Pengaruh Literasi Digital, Karakter Kewirausahaan Dan Keunggulan Bersaing Terhadap Keberhasilan Berwirausaha Pada Anggota AWBE Sidoarjo - Didik Nurhadi; Harti Harti; Siti Sri Wulandari (Jurnal Pendidikan Ekonomi, 2023)
In the 21st century, Indonesian MSMEs must be able to compete in marketing in the digitalization era. The purpose of this study was to determine and analyze the effect of digital literacy, competitive advantage and entrepreneurial character on the entrepreneurial success of AWBE members. Research that applies a descriptive quantitative approach. The descriptives that will be presented in this study are to find out how much influence the independent variables have on the dependent variable. The population in this study is 143 members with a sample in this study is 50. Sampling using purposive sampling. Data collection was carried out using questionnaires and observation. Instrument trials using validity and reliability tests. The data analysis technique in this study used multiple linear regression analysis techniques. Digital literacy and competitive advantage have a significant effect on the entrepreneurial success of members of the Sidoarjo Bringin Emas Entrepreneur Association. Meanwhile, entrepreneurial character does not significantly influence the entrepreneurial success of members of the Bringin Emas Sidoarjo Entrepreneurial Association. However, the results of the study show that there is a simultaneous significant influence between digital literacy, entrepreneurial character and competitive advantage on entrepreneurial success of 84.3%.